The relationship between attitude towards money, financial literacy and debt management with young worker's financial well-being - Abdullah, Nuraini; Sabri, Mohamad Fazli; Muhammad Arif, Afida Mastura (Universiti Putra Malaysia Press, 2019)
Malaysia has since undergone a lot of changes that are affecting its economic structure such as the rising cost of living which is an irreversible phenomenon. Coupled with the rise in the cost of production is the increased in indebtedness putting young worker’s financial well-being at stake. This article attempts to analyse the relationship between attitudes towards money, financial literacy and debt management towards financial wellbeing of young workers. Multi-stage random sampling technique was used for this study in the centre zone of Malaysia. A total of 508 respondents aged 40 and below was selected. Analysis using Pearson’s correlation showed that there were a positive relationship between financial literacy, debt management, attitudes towards money (inadequacy, effort/ability and retention) towards financial well-being. While, multiple regression results showed that all eight variables explained 27.4% of the variance of financial well-being whereby the variable of attitude towards money that is the dimension of ability/effort have a unique contribution towards financial well-being.